Comparative transcriptome analysis of two pomelo accessions with different parthenocarpic ability provides insight into the molecular mechanisms of parthenocarpy in pomelo (Citrus grandis) - Zhao, Keke; Zhang, Yunchun; She, Sulei; Yang, Ziwei; Zhang, Yue; Nie, Weiping; Wei, Xu; Sun, Haiyan; Dang, Jiangbo; Wang, Shuming; Wu, Di; He, Qiao; et al. (Frontiers in Plant Science, 2024)
Parthenocarpy is an important way for seedless fruit production in citrus. However, the molecular mechanism(s) of parthenocarpy in pomelo is still unknown. Our initial study found significantly different parthenocarpic abilities in Guanximiyou (G) and Shatianyou (S) pomelo following emasculation, and an endogenous hormone content assay revealed that indole-3-acetic acid (IAA), gibberellic acid (GA3) and zeatin (ZT) jointly promoted fruit expansion and cell division in parthenocarpic pomelo (G pomelo).To unravel the underlying molecular mechanism(s), we conducted the first transcriptome analysis on the two pomelo accessions at these two critical stages: the fruit initiation stage and the rapid expansion stage, in order to identify genes associated with parthenocarpy. This analysis yielded approximately 7.86 Gb of high-quality reads, and the subsequent de novo assembly resulted in the identification of 5,792 DEGs (Differentially Expressed Genes). Among these, a range of transcription factor families such as CgERF, CgC2H2, CgbHLH, CgNAC and CgMYB, along with genes like CgLAX2, CgGH3.6 and CgGH3, emerged as potential candidates contributing to pomelo parthenocarpy, as confirmed by qRT-PCR analysis. The present study provides comprehensive transcriptomic profiles of both parthenocarpic and non-parthenocarpic pomelos, reveals several metabolic pathways linked to parthenocarpy, and highlights the significant role of plant hormones in its regulation. These findings deepen our understanding of the molecular mechanisms underlying parthenocarpy in pomelo.